Circular RNA Expression Alteration and Bioinformatics Analysis in Rats After Traumatic Spinal Cord Injury - Qin, Chuan; Liu, Chang-Bin; Yang, De-Gang; Gao, Feng; Zhang, Xin; Zhang, Chao; Du, Liang-Jie; Yang, Ming-Liang; Li, Jian-Jun (Frontiers in Molecular Neuroscience, 2019)
Spinal cord injury (SCI) is mostly caused by trauma. As primary mechanical injury is unavoidable in SCI, a focus on the pathophysiology and underlying molecular mechanisms of SCI-induced secondary injury is necessary to develop promising treatments for SCI patients. Circular RNAs (circRNAs) are associated with various diseases. Nevertheless, studies to date have not yet determined the functional roles of circRNAs in traumatic SCI. We examined circRNA expression profiles in the contused spinal cords of rats using microarray and quantitative reverse transcription-PCR (qRT-PCR) then predict their potential roles in post-SCI pathophysiology with bioinformatics. We found a total of 1676 differentially expressed circRNAs (fold change≥2.0; P<0.05) in spinal cord 3 days after contusion using circRNA microarray; 1261 circRNAs were significantly downregulated, whereas the remaining 415 were significantly upregulated. Then, five selected circRNAs, namely, rno_circRNA_005342, rno_circRNA_015513, rno_circRNA_002948, rno_circRNA_006096, and rno_circRNA_013017 were all significantly downregulated in the SCI group after verification by qRT-PCR, demonstrating a similar expression pattern in both microarray and PCR data. The next section of the study was concerned with the prediction of circRNA/miRNA/mRNA interactions using bioinformatics analysis. In the final part of the study, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated carbohydrate metabolic process was one of the most significant enrichments and meaningful terms after GO analysis, and the top two signaling pathways affected by the circRNAs-miRNAs axes were the AMP-activated protein kinase (AMPK) signaling pathway and the peroxisome related pathway. In summary, this study showed an altered circRNA expression pattern that may be involved in physiological and pathological processes in rats after traumatic SCI, providing deep insights into numerous possibilities for SCI treatment targets by regulating circRNAs.